Confirmation and dissection of QTL controlling resistance to malaria in mice - Hernández Valladares, M.; Naessens, Jan; Gibson, John P.; Musoke, A.J.; Nagda, S.M.; Rihet, P.; Ole-MoiYoi, O.K.; Iraqi, F.A. (Springer, 2004)
We developed an F(11) AIL population from an F(1) cross of A/J (susceptible) and C57BL/6J (resistant) mouse strains. One thousand F(11) mice were challenged with P.c. chabaudi 54X, and 340 mice selected from the phenotypic extremes for susceptibility and resistance were genotyped for microsatellite markers on Chromosomes (Chrs) 5, 8, and 17. QTL originally detected in backcross and F(2) populations were confirmed on the three chromosomes within narrower genomic regions, by maximum likelihood and regression analyses. Each of the previously mapped QTL on Chrs 5 and 17 resolved into two linked QTLs. The distal and proximal QTLs on Chrs 5 and 17, respectively, map to the previously reported QTL.